How an Online Teaching Community Supports and Equips Interprofessional Graduate Faculty. Issue 1 (24th September 2022) - Pearce, Michelle J.; Cestone, Christina
Abstract : Introduction: Learning communities have been shown to help strengthen teaching skills, innovation, and scholarship. We sought to understand the impact of an online teaching community among interprofessional graduate faculty at a health professions university, notably in the context of COVID-19. Methods: The University of Maryland, Baltimore's Online Teaching Community (OTC) was created in 2019 to provide peer-to-peer faculty support and resources for effective online teaching. The OTC meets monthly, online, for a 1-hour informal discussion including a 30-minute topical presentation related to online teaching. A brief impact survey was completed in May 2020, as well as a live poll in January 2021. Results: Membership doubled after the first year; the OTC becoming particularly relevant after COVID-19, including individuals across seven professional schools on campus. Faculty reported enjoying the sense of community, feeling supported as an online instructor, and learning strategies and sharing resources for online instruction. Discussion: An OTC can support, unite, and equip interprofessional graduate faculty members to teach online. The OTC described may be a helpful model for developing and implementing OTCs on other campuses.